Neurological Emergencies in Clinical Practice - Rana, Abdul Qayyum. (Springer London : Imprint: Springer, 2013)
Neurological Emergencies in Clinical Practice discusses neurological emergencies in a stepwise fashion including stabilizing the patient, identifying the cause, and treating the underlying cause. It is useful in several settings including the emergency room, hospital in-patient service as well as the intensive care unit. Neurological Emergencies in Clinical Practice has a wide appeal and relevance to disciplines including neurology, emergency medicine,critical care medicine,internal medicine and family medicine. Medical students and residents may use this convenient, pocket-sized book to prepare for and succeed in their training examinations and it is also useful for other house staff and practicing physicians.